Estudos sobre a fotodegradação de poluentes catalisada por semicondutores: avaliação do papel do dopante nitrogênio na atividade de TiO2 - Soares, Gabriela Byzynski (Universidade Federal de São Carlos, 2013)
The photodegradation of organic pollutants in water, catalyzed by semiconductors, is an important and well-known area but it is still necessary develop new materials showing visible photoactivity, in order to take advantage of solar energy. One important material that have gained attention in this field is TiO2 doped with nitrogen (N:TiO2), which absorbs in wavelengths until 450 cm-1. However, its photocatalytic activity is in discussion, and the mechanisms increasing its activity are not clear understood yet, such as when the dopant could be deleterious to the activity. Therefore, this work has as principal goal the discussion about TiO2 and N:TiO2 photocatalytic activity from consolidated literature evaluations and comparatively with electrochemical experiments, which can infer how electronic proprieties are modified in the doping process. For that, a simple method for TiO2 doping with nitrogen was developed, by modifying a polymeric precursor with urea. The predominant crystalline phase was anatase and the characterization indicated that the doping method was effective. The calcination temperature variation resulted in different N substitutional and interstitial quantities and the relation about both presented fundamental importance for the doped nanoparticles photocatalytic activity in visible light. Also, it was observed that visible activity is better associated with dye sensitizing mechanism than with oxidants radicals generation. Thus, electrochemical studies with solid electrodes produced by the same nanoparticles synthesized before (and not as thin films) were done, which showed lower less efficiencies for N:TiO2 electrode. It was also observed that the doping process reduces the semiconductor band gap energy and the Fermi level to more negatives potential values, decreasing the energetic barrier for electronic transfer between Fermi level and conduction band. These results confirmed the doping importance on the direct transfer electronic mechanism for the organic substrates over the hydroxyls radical generation mechanism, which is more common on the advanced oxidative process.
Pollutant photodegradation studies catalyzed by semiconductors: role of nitrogen doping in TiO2 activity
Keywords: Fotocatálise; Semicondutores; Óxido de titânio dopado com nitrogênio (NTiO2); CIENCIAS EXATAS E DA TERRA::QUIMICA